Capturing finance : arbitrage and social domination - Hardin, Carolyn F., 1979- (Duke University Press, 2021)
"Carolyn Hardin offers a new way of understanding arbitrage--the trading practice that involves buying assets in one market at a cheap price and immediately selling them in another market for a profit--as a means of showing how its reliance upon taking on risk is fundamental to financial markets."--